Розробка мобільного додатку для діагностики атопічного дерматиту - Трубіцин, О. О.; Цзяо Ханькунь; Аврунін, О. Г. (ХНУРЕ, 2021)
Today in Ukraine there is a significant need to develop software for doctors treating children with atopic dermatitis. The project of the information system AtD 1.0 offered in this work is based on the principle of client-server technology. The server part is a system for storing medical diagnostic information, images of the affected areas of the skin. The client part of the system provides the doctor with data on the observed patients in a convenient, structured form. The client part of AtD 1.0 system based on React Native UI framework
Keywords: додаток мобільний; дерматит атопічний; діагностика